Pernikahan “Pada Gelahang” - Windia, Wayan P. (Badan Riset dan Inovasi Daerah Provinsi Bali, 2018)
Bali has changed. The world is no longer partially controlled by men but there are forms of marriage where both the bride and groom act as purusha (the power of patriarchy) or have the same rights and obligations between them. This qualitative study found that the number of bride and groom couples in Bali who choose the form of marriage